Peningkatan penelitian ekokritik tahun 2014—2024: Sebuah analisis bibliometrik - Nia Ifatul Mufidah; Widyastuti Purbani; Ari Nurhayati; Isti Haryati (Diglosia)
This study uses a bibliometric approach to analyze the rising trend of ecocriticism research over the past decade. A total of 314 articles were selected based on the keyword ecocriticism from the arts and humanities fields indexed in Scopus between 2014—2014. The study employs bibliometric analysis with the assistance of VOSViewer to reveal patterns and trends in ecocriticism research. The findings are as follows: ecocriticism studies have steadily increased from 2014 to 2024, with a significant surge observed in 2023. Green Letters and CLCWeb were identified as the primary journals publishing ecocriticism-related research. The most productive authors are Dellacasa, Raihanah, and Wardani. The year 2021 recorded the highest scientific impact (h-index 5; g-index 9), while 2022 stood out with the highest number of citations (75 citations across 23 articles), with the most cited article being Arafah et al. (2021), titled Saving the Environment: Environmental Lessons in Colin Thiele’s February Dragon. Geographically, the United Kingdom dominated publication output, whereas Indonesia recorded the highest citation count. The most frequently emerging themes include climate change, environmental degradation, anthropocentrism, ecocentrism, biocentrism, and ecofeminism. This bibliometric analysis also highlights the potential of ecocriticism, an interdisciplinary approach to fostering environmental awareness and informing public policy.